Rare diseases and the quality of life of caregivers - Michalík, Jan (Social Welfare: Interdisciplinary Approach, 2012)
The quality of life of persons caring for a family member with rare disease is discussed in the article and the results of the quantitative research (N = 298) in the Czech Republic are presented. The idea of the research is to determine basal psycho-social markers defining the quality of life of persons caring for a family member with rare disease and describe phenomena characterizing the conception of understanding the term quality of life by representatives of the target group (and compare this conception with how the term is understood by the intact population). Long-term care for a child with a serious, incurable disease means a significant change of life situation including not only personal growth, but also social, partner, health and economic associations. In the present research it has been focused on the existence of states and changes that were evaluated by caregivers themselves.
Keywords: quality of life; children with rare diseases; socio-psychological stability; expectations